Significance of exosomes in hepatocellular carcinoma - Wang, GuoYun; Luo, GaiXiang; Zhao, MeiJing; Miao, HuiLai (Frontiers in Oncology, 2022)
Among the most prevalent cancers in the world, hepatocellular carcinoma (HCC) has a high mortality rate. The diagnosis and management of HCC are presently hindered by difficulties in early detection and suboptimal treatment outcomes. Exosomes have been shown to play an important role in hepatocarcinogenesis and can also be used for diagnosis and treatment. In this review, we discussed the research progress on exosomes in hepatocarcinogenesis development, tumor microenvironment remodeling, treatment resistance, and immunosuppression. HCC can be diagnosed and treated by understanding the pathogenesis and identifying early diagnostic markers. This review will be a significant reference for scholars with an initial understanding of the field to fully understand the role of exosomes in the organism.